Karakteristik Kesehatan Mental Pada Remaja Disabilitas Di SLBN Jeneponto - Nurul Mutmainnah Akhmad; Mansur Sididi; Hasriwiani Habo Abbas (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Adolescents with disabilities are a vulnerable group experiencing various mental health problems due to physical, intellectual, and social limitations that can affect their ability to adapt and interact with the environment. Mental health disorders in adolescents with disabilities can include emotional problems, anxiety, hyperactivity, and obstacles in social relationships, with some cases reaching clinical significance. This study aims to describe the characteristics of mental health in adolescents with disabilities at SLBN Jeneponto. This study used a quantitative descriptive design implemented at SLBN 1 Jeneponto and SLBN 2 Jeneponto. The study population was all 97 students with disabilities enrolled in both schools. The study sample was determined using a total sampling technique. Data were collected using a questionnaire and analyzed univariately using SPSS. The results showed that the majority of adolescents with disabilities had undisturbed mental health (61 respondents (62.9%)), while 36 respondents (37.1%) experienced mental health disorders, some of which were clinically significant. Based on mental health characteristics, the majority of respondents experienced emotional instability (58.8%), anxiety (59.8%), did not experience hyperactivity (55.7%), had unrelated peers (53.6%), and received a democratic parenting style from their parents (53.6%). This study concluded that although the majority of adolescents with disabilities had stable mental health, a significant proportion still experienced emotional problems and anxiety, warranting targeted support. Therefore, support from families, schools, and the social environment is needed to maintain and improve the mental health of adolescents with disabilities.